2021
DOI: 10.1080/13102818.2021.1901610
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression pattern of alkaline/neutral invertase gene family inDendrobium catenatum

Abstract: Alkaline/neutral invertase (NI) proteins irreversibly break down sucrose into glucose and fructose and play a vital role in carbohydrate and plant growth and development. Currently, a comprehensive understanding of NI genes in Dendrobium catenatum is lacking. After genome-wide identification and prediction, nine DcNI genes were identified and named DcNI1-DcNI9. Through comprehensive analysis of gene structure, amino acid sequence, conserved motif and phylogenetic tree, it was found that the DcNI gene family ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Numerous efforts have been made to manipulate the expression of genes encoding the key regulatory enzymes, transcriptional factors, and other regulatory molecules that are directly or indirectly involved in CIS with variable degrees of success in reducing RS accumulation during CIS (Schwimmer et al, 1961;Sowokinos, 2001a;Geigenberger et al, 2004;Liu et al, 2010;Brummell et al, 2011;Liu et al, 2013;McKenzie et al, 2013;Zhang et al, 2013;Shivalingamurthy et al, 2018;Shi et al, 2021, Shi et al, 2022. Vacuolar acid invertase (vaINV), catalyzing the penultimate step, has been identified as one of the major factors involved in CIS (Zrenner et al, 1996;Matsuura-Endo et al, 2004;McKenzie et al, 2005;Liu et al, 2021). A few studies reported considerable improvement of CIS by down regulation of the StvaINV expression (Bhaskar et al, 2010;Wiberley-Bradford et al, 2014;Zhu et al, 2014;Hameed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous efforts have been made to manipulate the expression of genes encoding the key regulatory enzymes, transcriptional factors, and other regulatory molecules that are directly or indirectly involved in CIS with variable degrees of success in reducing RS accumulation during CIS (Schwimmer et al, 1961;Sowokinos, 2001a;Geigenberger et al, 2004;Liu et al, 2010;Brummell et al, 2011;Liu et al, 2013;McKenzie et al, 2013;Zhang et al, 2013;Shivalingamurthy et al, 2018;Shi et al, 2021, Shi et al, 2022. Vacuolar acid invertase (vaINV), catalyzing the penultimate step, has been identified as one of the major factors involved in CIS (Zrenner et al, 1996;Matsuura-Endo et al, 2004;McKenzie et al, 2005;Liu et al, 2021). A few studies reported considerable improvement of CIS by down regulation of the StvaINV expression (Bhaskar et al, 2010;Wiberley-Bradford et al, 2014;Zhu et al, 2014;Hameed et al, 2018).…”
Section: Introductionmentioning
confidence: 99%